Understanding the Difficulties in Teaching Social Studies: A Systematic Literature Review - Yusra, Alfajri; Ananda, Azwar; Fatimah, Siti; Erianjoni, Erianjoni (Postgraduate School, Universitas Negeri Padang, 2021)
This article aims to understand the difficulties faced by educators in teaching social studies. In understanding these difficulties, this literature review explores relevant sources and analyzes existing findings. Some of the common difficulties identified include concept complexity, multidisciplinarity, and differences in students' backgrounds. In addition, this article also discusses some effective teaching strategies in overcoming these difficulties, such as problem-based approaches, use of technology, collaborative learning, and utilization of local resources. Through appropriate teaching strategies, educators can facilitate students' better understanding of social studies and help them develop critical thinking and a deep understanding of social, political and cultural dynamics. The knowledge gained from this literature review provides important insights for social studies educators in facing teaching challenges and improving the quality of learning. By deepening this understanding through further research, social studies educators can continuously improve their teaching practices and have a more positive impact on students' academic and social development.